Pengaruh Kemudahan, Promosi, Pengalaman dan Kepuasan Terhadap Minat Penggunaan Gopay di Tokopedia - Pradnyana, I Wayan Julianta; Putra, I Komang Trisna Eka; Yunita, I Made; Sugiartana, I Wayan (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
This study aimed to analyze the influence of ease of use, promotions, user experience, and user satisfaction on the intention to use GoPay on Tokopedia. With the growing adoption of digital technology in Indonesia, digital payment systems like GoPay have become a preferred option for e-commerce transactions. The scope of this study focused on Tokopedia users in Indonesia who had utilized GoPay as a payment method. Respondents were selected through purposive sampling, targeting active users who had previously used GoPay in their transactions. A total of 120 respondents participated in this study. The research employed a quantitative approach, utilizing Structural Equation Modeling (SEM) to examine the relationships between variables. The findings reveal that ease of use, promotions, user experience, and user satisfaction significantly influence the intention to use GoPay, with promotions identified as the most dominant factor. These insights contribute to GoPay’s marketing strategy, highlighting the importance of enhancing promotions and delivering a positive user experience to sustainably increase user interest.